Developing Topics of Experiential Activities in Defense and Security Teaching in Order to Develop Learners' Ability to Learn about Nature and Society - Minh Tien, Le; Sang, Hoang Van; Anh, Nguyen Ngoc (VNU Journal of Science: Education Research, 2023)
This article aims to propose a set of topics for experiential activities in defense and security teaching that can enhance learners' abilities to learn about nature and society. The article begins by highlighting the importance of defense and security education in shaping learners' understanding of the role of military and security forces in protecting the nation and society. The article then presents five topics for experiential activities, which include visiting security and military agencies, practical experience in military training, practicing emergency response skills, learning self-defense techniques, and engaging in social activities related to security. The article argues that these activities can not only help learners gain a better understanding of defense and security but also provide them with opportunities to develop essential skills such as decision-making, problem-solving, and collaboration. Furthermore, the article suggests that these activities can instill a sense of civic responsibility and a willingness to contribute to the community's safety and well-being. Overall, the article proposes that incorporating experiential activities into defense and security teaching can enrich learners' learning experiences and foster their abilities to learn about nature and society. By providing hands-on experiences and opportunities for practical application, defense and security education can prepare learners to be responsible and engaged citizens who understand the importance of national defense and community safety.